DYSREGULATION OF AMP-ACTIVATED PROTEIN KINASE SIGNALING IN ALZHEIMER’S DISEASE - Wang, Xin (Wake Forest University, 2018)
The etiology of Alzheimer’s disease (AD), one of the most grievous neurodegenerative disease, is still unclear despite decades of study and early diagnosis of this disease remains a challenge. Energy metabolic dysfunction has been found to be a distinct characteristic in Alzheimer’s disease, and may be the underlying pathogenic mechanism of Alzheimer’s disease. AMP-activated protein kinase (AMPK) is a master energy sensor which can sense the ratio of AMP/ATP and regulates catabolic and anabolic pathways to keep the energy metabolism in balance, and has been found to play an important role in the pathogenesis of Alzheimer’s disease. AMPK has 3 subunits, the α, β and γ. The α subunit is the catalytic subunit and has 2 isoforms, α1 and α2. Phosphorylation of α subunit determines the activity of AMPK. In this study, I found AMPKα2 was dysregulated in a vervet monkey model of Alzheimer’s disease, which exhibited AD-like pathologies, biochemical alterations and behaviors. Proteomic studies in this model showed that many of dysregulated proteins were metabolism-related and could be associated with AMPK signaling. I also found level of AMPKα1 was significantly deceased in the plasma of AD and mild cognitive impairment (MCI) patients as compared to healthy controls and the efficacy of AMPKα1 level in plasma to differentiate patients from controls was relatively high. In summary, this study found that AMPK signaling was dysregulated in a vervet monkey model of Alzheimer’s disease, which could be used as a tool for development of therapeutics of Alzheimer’s disease, and AMPKα1 was significantly decreased in the plasma of AD and MCI patients, indicating that AMPKα1 could serve as a biomarker for the early diagnosis of Alzheimer’s disease.
Keywords: Alzheimer's disease; AMPK; biomarker; model; non-human primate